Investigation of agronomic traits, dry matter remobilization and stress indices in promising bread wheat genotypes under salinity stress - Elias ARAZMJOO; Ashkboos AMINI SEFIDAB (Journal of Central European Agriculture, 2024)
Improving the crop yield by conventional breeding methods and selection of genetically modified genotypes are the basic approaches to produce tolerance against salinity stress. In total 20 wheat genotypes and cultivars in non-stress and salinity stress environments were evaluated during the cropping years of 2015-2016 in a randomized complete block design with three replications. The amount of dry matter during pollination and maturity stages was higher in non-stress conditions than in salinity stress. The results showed that exposure to salinity stress significantly increased dry matter remobilization and decreased current photosynthesis in wheat. The dry matter remobilization rate and its efficiency in genotypes No. 14, 16, and Arg cultivar and the dry matter remobilization ratio in genotypes No. 9, 5, and 14 were higher than others. Also, the Principal Component Analysis (PCA) showed that the first principal component (PC1) had a high positive correlation with grain yield under stress conditions (Ys) and MP, STI, GMP, HM, YI, and RSI indices, and the second principal component (PC2) had a high positive correlation with grain yield under non-stress conditions (Yp) and TOL and SSI indices. According to the biplot diagram, genotypes No. 16 and 14 with more value of PC1 and less value of PC2 identified as the most tolerant genotypes to salinity stress.